2021
DOI: 10.1093/plankt/fbab050
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic and functional differences between winter and summer crustacean zooplankton communities in lakes across a trophic gradient

Abstract: Despite increasing interest in winter limnology, few studies have examined under-ice zooplankton communities and the factors shaping them in different types of temperate lakes. To better understand drivers of zooplankton community structure in winter and summer, we sampled 13 lakes across a large trophic status gradient for crustacean zooplankton abundance, taxonomic and functional community composition and C/N stable isotopes. Average winter zooplankton densities were one-third of summer densities across the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 79 publications
2
8
0
Order By: Relevance
“…Along the depth gradient (Duluth Harbor, Chequamegon Bay, Duluth Entry, Madeline Island, McQuade Harbor), summer–winter densities varied 329‐, 53‐, 8‐, 10‐, and 33‐fold, respectively. The lower zooplankton densities we observed in winter agree with other studies (Hampton et al 2017; Kalinowska et al 2019; Kalinowska and Karpowicz 2020, Shchapov et al 2021) where winter zooplankton were reported to be 1.2‐ to 38‐fold lower compared to summer values. The reason for this large variability of summer‐to‐winter differences in zooplankton densities across systems is an open question, but our results suggest that shallow and productive systems that warm rapidly after ice‐off may display larger summer‐to‐winter variations than deeper and more oligotrophic ones.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Along the depth gradient (Duluth Harbor, Chequamegon Bay, Duluth Entry, Madeline Island, McQuade Harbor), summer–winter densities varied 329‐, 53‐, 8‐, 10‐, and 33‐fold, respectively. The lower zooplankton densities we observed in winter agree with other studies (Hampton et al 2017; Kalinowska et al 2019; Kalinowska and Karpowicz 2020, Shchapov et al 2021) where winter zooplankton were reported to be 1.2‐ to 38‐fold lower compared to summer values. The reason for this large variability of summer‐to‐winter differences in zooplankton densities across systems is an open question, but our results suggest that shallow and productive systems that warm rapidly after ice‐off may display larger summer‐to‐winter variations than deeper and more oligotrophic ones.…”
Section: Discussionsupporting
confidence: 92%
“…Deeper sites (especially Duluth Entry and Madeline Island) also had less seasonal variation in seston concentrations than shallow stations. This suggests that more productive and shallow regions of large lakes can maintain relatively high phytoplankton concentration during winter, an observation supported from studies of smaller lakes across productivity gradients (Hampton et al 2017; Shchapov et al 2021).…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations